BLOCK GRANT (DAU) AND POVERTY ALLEVIATION IN INDONESIA - Putri Bintusy Syathi; Fitriyani Fitriyani; Ermawati Ernawati (Syiah Kuala University, 2020)
AbstractDana Alokasi Umum (DAU) is the block grant allocated by central government to fill in the Fiscal gap as Indonesia implementing decentralization. The local government as mandated in the decentralization act can implement development program with the fund. Therefore, the fund can improve local economic activities and alleviate poverty in general. This study exercise econometrics model of regression to investigate the relationship between the DAU and poverty alleviation in Indonesia during 2000 to 2018. The result show that the fund only help to reduce poverty in lag time. Therefore, it implies the local government depend on the fund to activate the program in the region.